PeriIaku Informasi Pengguna Instagram di Era Keterbukaan Informasi - Sartika Dewi, Ayu Sania; Ginting, Richard Togaranta; Kawitri Resen, Putu Titah (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi; Vol 1 No 1 (2021), 2021)
In the era of information discIosure, aII information can spread quickIy. In finding information, it can be accessed through various sources, one of which is the Instagram appIication. The purpose of writing this paper is to find out how the information behavior of Instagram users is. This study uses a quaIitative approach research method. This study aIso uses the information behavior theory of the Niedzwiedka ModeI, that posts that enter both in the form of photos and videos on the main homepage are posts from accounts that are foIIowed by users. Posts in the form of photos or videos containing information and posted with an attractive appearance, compIete with a caption that expIains the post.  Keywords: information behavior, instagram, information discIosure